Program Pencegahan Penularan COVID-19 pada Komunitas Ibu Rumah Tangga dengan HIV di Surabaya - Hanna Tabita Hasianna Silitonga; Etha Rambung; Romauli Nainggolan; Gusto Benyamin Messakh; Keith Justine Thiotansen (University of Merdeka Malang, 2020)
Everyone was affected by COVID-19 pandemic, including housewives with HIV joined in Bu'Daya community. In management of COVID-19, patient's comorbid history was important because these patients could aggravate the condition of COVID-19. HIV was a chronic disease related to the immune system. Therefore, it was important for people with HIV to prevent infection of COVID-19. The problem faced by this community regarding COVID-19 was knowledge and attitudes of community members was not known yet. Therefore, efforts were needed to find out and improve understanding of COVID-19. The solution offered to this community was training and assistance regarding the prevention of COVID-19 through the